PEMANFAATAN SILIKA DARI PASIR PANTAI LINAU UNTUK MENGURANGI KADAR AMMONIUM DALAM LIMBAH CAIR TAHU - Chrisnia Nurbaiti; Rina Elvia; I Nyoman Chandra (ALOTROP, 2018)
The purpose of this study was to synthesize silica from Linau beach sand and its application as an adsorbent in reducing ammonium content in tofu liquid waste. Silica synthesis was carried out using the Sol-gel method using raw materials of 20 grams of refined sand, by dissolving sand into 160 mL NaOH 4 M while being heated and stirred constantly at 1050C for 90 minutes, and then filtered using filter paper. The residue obtained was calcined at 500oC for 30 minutes. The solid obtained is dissolved into 200 mL aqua DM so that it becomes a sodium silica solution. The sodium silicate solution was obtained, then added 1 M HCl solution drop by drop until it was obtained pH 7, and then left for 18 hours until a gel was formed and continued with washing using aqua DM and filtered with filter paper. The gel obtained was then dried at 1050C for 8 hours in the oven to obtain silica powder. Silica redemen produced from silica synthesis from Linau beach sand was obtained at 0.405%. The results showed that the synthesis silica from Linau beach sand was able to reduce ammonium content in tofu wastewater with the yield parameters in the form of tofu waste content decreasing at optimum mass 0, 25 grams, contact time 15 minutes with adsorption efficiency of 32.59%